2016
DOI: 10.1097/nne.0000000000000260
|View full text |Cite
|
Sign up to set email alerts
|

Broadening the Reach of Standardized Patients in Nurse Practitioner Education to Include the Distance Learner

Abstract: Using standardized patients (SP) presenting with a specific complaint has been a mainstay in health care education. Increased use of technology has facilitated the move of instruction from the on-campus classroom to distance learning for many nurse practitioner programs. Using interactive case studies provides distance learners SP encounters. This technologically facilitated encounter gives the distance learner the opportunity for integrative thinking and development of problem solving and clinical reasoning s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…A simulation with standardized patients (SPs) provides opportunities for students to apply their skills on persons trained to impersonate the characteristics of a real patient in a safe and controlled environment prior to taking care of real patients in clinic [13]. Teaching with SPs has many advantages, including increasing students’ communication skills with patients and with teammates [14], improving clinical reasoning [15], and reducing students’ anxiety and stress and increasing their self-efficacy and study motivation [16]. Therefore, students can develop critical-thinking skills through decision-making and problem-solving so as to maintain a safe training environment without worrying about injuring patients.…”
Section: Introductionmentioning
confidence: 99%
“…A simulation with standardized patients (SPs) provides opportunities for students to apply their skills on persons trained to impersonate the characteristics of a real patient in a safe and controlled environment prior to taking care of real patients in clinic [13]. Teaching with SPs has many advantages, including increasing students’ communication skills with patients and with teammates [14], improving clinical reasoning [15], and reducing students’ anxiety and stress and increasing their self-efficacy and study motivation [16]. Therefore, students can develop critical-thinking skills through decision-making and problem-solving so as to maintain a safe training environment without worrying about injuring patients.…”
Section: Introductionmentioning
confidence: 99%
“…Given these overall positive results, it seems clear that there are many reasons why nursing students may choose ODL for postgraduate education. Ballman et al suggest it allows registered nurses to pursue higher degrees without having to leave their clinical positions (15), and report that students demonstrate digital literacy and are comfortable with the online learning environment. Merrill describes today's nursing students as the NET Generation, a group that came of age in a "media-rich" world and expects to use online technologies in education; thus, faculty and nursing school curriculums must adapt to new learning preferences that may challenge traditional teaching methods (16).…”
mentioning
confidence: 99%
“…Development of learning communities [13,21,31,41,45]. 3. Connecting learning to improved clinical practice [15,17,26,28,38,54]. 4. Learning that leads to the best possible provision of care for people living with dementia [17,.…”
Section: Data Synthesis Of Key Featuresmentioning
confidence: 99%
“…It was frequently reported that learners who are engaged in Web-based studies require a level of commitment and willingness, the ability to develop self-direction, and a capacity for flexibility [14,[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]42,43]. The authors' evaluation of the learners' feedback regarding the DCC&TN emphasized similar challenges.…”
Section: Data Synthesis Of Key Featuresmentioning
confidence: 99%
See 1 more Smart Citation